The Feasibility of Museum Social Media for Millenial: A Case Study in Sonobudoyo and Sandi Museums Yogyakarta Indonesia - Ayu Hellena Cornellia; Hary Hermawan; Nikasius Jonet Sinangjoyo; Prihatno (Media Wisata, 2022)
The raising awareness of social media museums has developed gradually. A previous study related to the topic which found out that it was not properly managed is now defeated with a better solution of having a consultant or outsource staff in the museum. As social media has a great role in improving museum visitors and awareness in society, a deeper understanding and method of its application is explored in this study. The general purpose of this research is to find out the suitable Social Media Marketing method for Millennial targets as they are very active on social media compared to other generations. The method of this research was mix qualitative-quantitative approach and the sample was Sonobudoyo and Sandi museums in Yogyakarta, Indonesia was selected based on the active use of social media especially Instagram. The respondents were thirty-nine Instagram followers of Sonobudoyo and thirty-eight Instagram followers of Sandi. This study concludes that both museums have a good implementation of Social Media Marketing as the number of Instagram followers is above 5,000. It is suggested that the result of this study could provide input for other museums in Indonesia to become preferred tourism destinations while carrying out proper Social Media Marketing (SMM) especially for Millennials through updated and exciting content.